Recent Decadal Weakening of the Summertime Rainfall Interannual Variability Over Yellow-Huaihe River Valley Attributable to the Western Pacific Cooling - Lu, Wei; Zhu, Yimin; Ha, Yao; Zhong, Zhong; Hu, Yijia (Frontiers in Earth Science, 2022)
This study focuses on the interdecadal transition of summer rainfall interannual variability over the Yellow-Huaihe River valley (YHRV). It is found that the interannual variability of summer rainfall over the YHRV becomes significantly weakened after the late 2000s. In the decade before the late 2000s (hereafter P1), the variance is 1.28 mm d−1 and the mean value of interannual variability is 1.49 mm d−1. In the decade after the late 2000s (P2), the variance is 0.35 mm d−1 and the mean value of interannual variability is 0.62 mm d−1. The variance and mean value of summer rainfall interannual variability have considerably decreased by 72.7% and 58.4% since the late 2000s, respectively. The reasons for the aforementioned interdecadal transition are explored. The results show that the interdecadal shift of the East Asian jet stream axis and the western Pacific subtropical high (WPSH) are two major factors leading to the interdecadal transition of summer rainfall interannual variability over the YHRV. The northward shift of the jet stream axis, which resembles the Pacific-Japan (PJ) pattern, suppresses the development of summer rainfall over the YHRV. The interannual oscillation of WPSH in P1 is more significant than that in P2, which is consistent with the weakened interannual variability of summer rainfall in P2. Further analysis reveals that the modulation factors responsible for the above changes are El Niño in its decaying phase in the equatorial central eastern Pacific and the warming in the Maritime continent and the western Pacific (WP) in P1. While in P2, the primary modulation factor is La Niña in its developing phase in the equatorial central eastern Pacific. As for the mechanism of the growth of summer rainfall in P1 positive years, the WP warm pool and El Niño in its decaying phase strengthen the Walker circulation in the tropical Pacific and induce Hadley circulation, whose ascending branch over the YHRV provides a favorable condition for the development of rainfall. At the same time, the northward propagation of Rossby waves in response to the above SSTA pattern suppresses convective activities over the Northwestern Pacific (NWP), which indirectly intensifies the WPSH. As a result, the PJ pattern is triggered and provides a favorable large-scale circulation condition for the growth of rainfall.